(untitled) (Huellas, 2025)
In Pampean territories, urban centers with robust electrical infrastructure contrast with regions where energy services are precarious. In the latter, the photovoltaic potential and the stimuli to renewable generation represent opportunities for the development of diverse projects. This paper aims to analyze photovoltaic projects in the provinces of Buenos Aires, Córdoba and Santa Fe, considering their contribution to solve energy deficits and the participation of different actors. Field observation and interviews with key informants were carried out. In addition to counteracting shortcomings, photovoltaic projects allow for the advancement of community experiences that articulate multiple actors. The diversity of initiatives identified together with the analysis of their characteristics made it possible to recognize projects of different modalities.